A revision of unrevised taxon names in the former genus Taxilejeunea (Marchantiophyta: Lejeuneaceae) from Asia - Lee, Gaik Ee; Bechteler, Julia; Heinrichs, Jochen (Phytotaxa, 2018)
Recent molecular work has shown that the genus Taxilejeunea is a synonym of Lejeunea. This study deals with the status of unrevised taxon names in Taxilejeunea from Asia. Six species are transferred to Lejeunea (L. compressiuscula, L. javanensis, L. koordersii, L. giulianettii, L. splendida, L. tjibodensis) and two new varieties, L. discreta var. gracilipes, L. pulchriflora var. nymannii, are described. Seven new synonyms are proposed: Taxilejeunea cuspidata Steph. ex Schiffn. [= L. stevensiana (Steph.) Mizut.], T. deflexa Steph. [= L. microloba Taylor], T. laxiretis (Steph.) Eifrig [= L. sordida (Nees) Nees], T. longirostris Herzog [= L. mizutanii Grolle], T. obtusistipula Steph. [= L. albescens (Steph.) Mizut.], T. stephanii Eifrig [= L. discreta Lindenb.] and T. umbilicata f. brevirostris Eifrig [= L. umbilicata (Nees) Nees].